Use of Giant Bilobed Flap for Advanced Head and Neck Defects - Mourad, Moustafa; Arnaoutakis, Demetri; Sawhney, Raja; Chan, David; Ducic, Yadranko (Facial Plastic Surgery, 2016)
This article aims to review the use of giant bilobed flaps in the reconstruction of various large defects within the head and neck. A single case series study with chart review was performed. Various facial, neck, and mentum defects were documented, and closure was accomplished through a variety of medially and laterally based giant bilobed flaps. Preoperative and postoperative photography, as well as intraoperative planning, was performed. A total of 23 patients were able to achieve closure of facial, head, and neck defects with single-stage closure through the use of a giant bilobed flap. No tissue expanders, free tissue transfers, or skin grafts were required to achieve final closure, with acceptable cosmetic and functional results. Bilobed-shaped flaps allow for local tissue transfer in regions of otherwise limited tissue laxity and mobility, classically designed and utilized in the region of the nose. We describe its applicability to closure of large head and neck defects that may otherwise require free tissue transfer or the use of tissue expanders.
Keywords: Mohs excision; bilobed flap; single-stage closure; facial defects